Distinct pathways of LPS-induced NF-kappa B activation and cytokine production in human myeloid and nonmyeloid cells defined by selective utilization of MyD88 and Mal/TIRAP. - Andreakos, E; Sacre, S; Smith, C; Lundberg, A; Kiriakidis, S; Stonehouse, T; Monaco, C; Feldmann, M; Foxwell, B (2004)
How lipopolysaccharide (LPS) signals through toll-like receptors (TLRs) to induce nuclear factor (NF)-kappa B inflammatory cytokines in sepsis remains unclear. Major candidates for that process are myeloid differentiation protein 88 (MyD88) and MyD88 adaptor-like/TIR domain-containing adaptor protein (Mal/TIRAP) but their role needs to be further defined. Here, we have examined the role of MyD88 and Mal/TIRAP in primary human cells of nonmyeloid and myeloid origin as physiologically relevant systems. We found that MyD88 and Mal/TIRAP are essential for LPS-induced I kappa B alpha phosphorylation, NF-kappa B activation, and interleukin 6 (IL-6) or IL-8 production in fibroblasts and endothelial cells in a pathway that also requires IKK2. In contrast, in macrophages neither MyD88, Mal/TIRAP, nor I kappa B kinase 2 (IKK2) are required for NF-kappa B activation or tumor necrosis factor alpha (TNF alpha), IL-6, or IL-8 production, although Mal/TIRAP is still involved in the production of interferon beta (IFN beta). Differential usage of TLRs may account for that, as in macrophages but not fibroblasts or endothelial cells, TLR4 is expressed in high levels at the cell surface, and neutralization of TLR4 but not TLR2 blocks LPS signaling. These observations demonstrate for the first time the existence of 2 distinct pathways of LPS-induced NF-kappa B activation and cytokine production in human myeloid and nonmyeloid cells defined by selective utilization of TLR4, MyD88, Mal/TIRAP, and IKK2, and reveal a layer of complexity not previously expected.